TELAAH KEMAMPUAN SANTRI DALAM MEMBACA KITAB FATHUL QORIB MELALUI MATERI NAHWU KITAB AL- MIFTAH LIL ULUM DI PONDOK PESANTREN MIFTAHUL ULUM AL-HIKMAH SAMPANG - Yakin, Ainul; Suhri, Moh. (Universitas Al-Amien Prenduan, 2024)
The ability to read the yellow book (turats) is a starting point for centers to understand the meaning and content of the Arabic texts they learn. They will have them when they have the knowledge of the al-Qowaid al-Nahwiyah dan Shorfiyah. Fathul Qorib is one of the classic books known by the centurions among the so-called Yellow Book. It is the Pondok Pesantren Miftahul Ulum Al-Hikmah in Sampang that undertakes efforts to improve the readings of the Book of Fathul Qorib through the learning of the material of the book of Fatul lil Ulum which needs to be examined. The focus of this research is to explore the ability of the centurion to read the book of Fathul Qurib through the Nahwu book of Fathul lil Ulum in the Pondok Pesantren Miftahul Ulum Al-Hikmah Sampang. This research uses a qualitative approach with a type of qualitatively-descriptive research. As for the data source, the primary data that comes from the teacher's informant is also from the 5th and 6th classes and the data skunder is the documentation of images and video recordings of learning and evaluation activities. Data analysis techniques by collecting data obtained from the results of observations, interviews and documentation, data condensate and data presentation or data verification are then analyzed to obtain conclusions results of research.The results of the research concluded that santri can read the book of Fathul Qorib and understanding of the theory of nahwu increased with the presence of the application of the nahwu book of Al-Miftah lil Ulum, This was proved by santri who previously had not been able to know at all the theories of Nahwu such as isim, fi’il and huruf can be e-tahui. In addition, he is able to practice the results of the material understanding of the Book of Al-Miftah when reading the book of Fathul Qorib. Santri can distinguish the position of the sentences that are in the book of Fathul Qorib, such as the isim, fi’il and huruf.